CONTRIBUTION TO THE KNOWLEDGE OF THE GEOMETRID MOTHS (LEPIDOPTERA: GEOMETRIDAE LEACH, 1815) OF MONTENEGRO AND SERBIA (Acta Entomologica Serbica, 2021)
The results of the faunal exploration of Geometer Moths (Lepidoptera, Geometridae) in the area of Montenegro and Serbia are reported. Based on fieldwork conducted in the past 50 years, data for 71 species are presented. Wherever necessary, comments are provided concerning ovipositional and nutritional plants, as well as illustrations of adults and genital armature. In Montenegro, several species have been recorded for the first time.